All‐Optical Detection of Spin Pumping and Giant Interfacial Spin Transparency in Co2Fe0.4Mn0.6Si/Pt Heterostructure. Issue 7 (21st May 2022) - Dutta, Koustuv; Panda, Surya N; Seki, Takeshi; Pan, Santanu; Takanashi, Koki; Barman, Anjan
Abstract: Active control over the generation and manipulation of pure spin current has propelled drastic transformation in new generation spintronics. Spin pumping is one of the favored mechanisms to generate pure spin current and its efficiency can be parameterized in terms of spin‐mixing conductance ( G ↑ ↓ G_ ) and spin‐diffusion length ( λ ). Here, using all‐optical time‐resolved magneto‐optical Kerr magnetometry, spin pumping in a ferromagnetic Heusler compound (Co2 Fe0.4 Mn0.6 Si (CFMS))/Pt heterostructure is investigated keeping in mind the small intrinsic damping and stable spin‐polarized band structure at the Fermi level of the CFMS and excellent spin‐sink property of Pt. The thickness‐dependent evolution of Gilbert damping is modeled using ballistic and diffusive spin transport frameworks to extract G ↑ ↓ G_ and λ . Finally, a giant value of interfacial spin transparency up to 0.87 ± 0.02 combined with small intrinsic damping of 0.0039 ± 0.0004 promote the CFMS/Pt heterostructure as a champion material for the development of advanced spin‐orbitronic devices. Abstract : In this article, the spin pumping phenomenon in the Co2 Fe0.4 Mn0.6 Si/Pt interface is investigated by employing an all‐optical time‐resolved magneto‐optical Kerr effect measurement. A giant interfacial spin transparency and a high spin mixing conductance are found which are pivotal for spin‐orbitronic device applications with high energy efficiency.